Perkuatan Lereng pada Sempadan Sungai Jl. Sultan Agung Kabupaten Jember dengan Dinding Penahan Tanah Kantilever - Luqman Hakim; Paksitya Purnama Putra; Dwi Nurtanto (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2021)
The land collapsed on Jl. Sultan Agung, Jompo, Jember Regency was reported. A team from the Regional Disaster Management Agency (BPBD) found cracks in the ground under a shop since February 2019. This incident resulted in a landslide of a road with approximately 45 meters long and 10 meters wide that it blocked the river flow, and nine shophouses, which are the assets of the Jember Regency government, collapsed as deep as approximately 4 meters. The cantilever type retaining wall is designed in the landslide area as an effort to revitalize the banks of Jompo river on Jalan Sultan Agung. Cantilever wall design stability refers to SNI 8460: 2017 and was assisted by using the GEO 5 program. The stability of cantilever walls against overturning shows a safety factor value of 3.72 that greater than 2 (safe condition), whereas the stability of cantilever walls against sliding was 1.61 that greater than 1.5 (safe condition), and the stability of the bearing capacity was 8.18 that greater than 3 (safe condition). Cantilever wall structure using concrete quality (Fc ') 40 MPa, and reinforcement quality (Fy) 420 Mpa, with a diameter and a distance of 25 mm and 125 mm respectively. Additional reinforcement was given to the Cantilever Wall, i.e. a bore-pile with a diameter of 60 cm which was fixed to a depth of 6 meters.